PROSPECTIVIDAD DE HIDROCARBUROS EN LA CUENCA VAUPÉS-AMAZONAS, COLOMBIA (2013)
The assessment of hydrocarbon prospectivity in the Vaupés-Amazon Basin frontier with an area of 155,000 km^2 indicates that the southern area presents the highest gas potential, and that is also related with the oil and gas potential in the Solimöes Basin in Brazil. The potential hydrocarbon reservoirs are related to compressive structures, which were identified in seismic lines of the Vaupes-Amazonas Basin, and formed during the Hercinian orogeny. The Geochemical models indicate that hydrocarbons were generated in the organic-rich Devonian shales in the late Permian and migrated later in the early Mesozoic. High TOC contents and high maturity maturation levels found in the Devonian organic-rich shales in the Solimöes Basin, indicate that the Vaupés-Amazon Basin may also have a potential for unconventional deposits of shale gas type.